Biomechanics of gymnastics - Nyman, E. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
Given that the gymnast pushes the boundaries of biomechanical tolerances of the body`s tissues, it should come as little surprise that the history of the field of biomechanics is fairly well correlated with the sport`s origins. While gymnastics was first described as an athletic practice in the times of the ancient Greeks and later Romans, so too was the field of biomechanics, as the earliest traces (study of musculoskeletal anatomy) of the discipline dates back to as early as fourth century BC via Aristotle`s De Motu Animalium. Leonardo da Vinci and later Giovanni Borclli further catapulted biomechanical research in the fifteenth and seventeenth centuries, respectively. Since then, the field has evolved in leaps and bounds. Ironically, these leaps and bounds may be directly tied to the advancements the sport of gymnastics has experienced, as both entities were well established by the mid-eighteenth century in part due to the efforts of Eadweard Muybridge (a forefather of modern biomechanics) and Pierre de Coubertin (considered the father of the modern Olympic Games). While the histories of both biomechanics and gymnastics can be individually traced back centuries, relatively more modern ages have continued to see interactions between these entities. While numerous authors have scientifically evaluated gymnastics performance from a sports science, exercise physiology, and biomechanical basis, few have been as active in the space during the late twentieth and early twenty-first centuries as Dr. William Sands. Dr. Sands` work has spanned three decades and has enlightened the coach and practitioner on biomechanical principles and performance enhancement relative to the modern sport. To date, he has published a multitude of empirical research articles relative to the sport of gymnastics - ranging from skill biomechanics to exercise physiology, to electromyography (EMG) - many of which will benefit the clinical practitioner in this field and may be considered requisite reading,